2019
DOI: 10.2174/1874210601913010346
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dental Implants Placements between Lateral and Crestal Sinus Lift Techniques: A Split-Mouth Study

Abstract: Background: Bone atrophy and pneumatization of the maxillary sinus resulting from tooth loss, associated with low bone density in the region, do not usually allow adequate quantity and quality for the installation of osseointegrated implants. Objective: To evaluate the efficacy of crestal and lateral sinus lift techniques which are performed on same patients. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Different aspects of possible risk factors were evaluated to provide a comprehensive understanding about implant loss in TSFE sites. Previous studies focusing on implant prognosis after TSFE have reported survival rates ranging from 90% to 100% (Al‐Almaie & Kavarodi, 2019; Antonoglou et al, 2018; Rammelsberg et al, 2020; Tan et al, 2008). Likewise, our study results showed a satisfactory overall 3‐year implant survival rate of 96.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Different aspects of possible risk factors were evaluated to provide a comprehensive understanding about implant loss in TSFE sites. Previous studies focusing on implant prognosis after TSFE have reported survival rates ranging from 90% to 100% (Al‐Almaie & Kavarodi, 2019; Antonoglou et al, 2018; Rammelsberg et al, 2020; Tan et al, 2008). Likewise, our study results showed a satisfactory overall 3‐year implant survival rate of 96.9%.…”
Section: Discussionmentioning
confidence: 99%